The effect of angiotensin 1-7 and losartan on renal ischemic/reperfusion injury in male rats - Tahereh Safari; Mohamad Reza Shahraki; Saideh Miri; Nasime Mirakzehi Bakhshani; Abbass Ali Niazi; Gholam Reza Komeili; Hossain Bagheri (Wolters Kluwer Medknow Publications, 2019)
Ischemia/reperfusion (I/R) is a major cause of acute kidney injury. Several studies have shown that renin angiotensin (Ang) system and activation of Ang II type 1 receptor (AT1) are involved in various forms of kidney diseases. Likewise, Ang 1-7 as a physiologic antagonist of AT1 and losartan could possibly protect the kidney against I/R damage. Therefore, we investigated renal injury by administering the drugs before and after I/R. Fifty-four male Wistar rats were randomly assigned to five groups as follows. 1, Sham operated; 2, saline group (as a control group); 3, losartan group; 4, Ang 1-7group; and 5, Ang 1-7 + losartan simultaneously. It should be noted that groups 2-5 consisted of two separate I/R-induced subgroups both receiving medication where the first groups received the treatment 15 min before induction of I/R while the medications were given to the second groups immediately after induction of I/R. Twenty four h after I/R, blood samples were collected, and then levels of serum urea nitrogen (BUN), creatinine (Cr), nitrite, malondialdehyde (MDA), lactate dehydrogenase (LDH) and total antioxidant capacity (TAC) were measured. Likewise, nitrite, MDA and TAC were measured in the homogenized kidney tissues. After the induction of I/R, the BUN, Cr, LDH, and kidney tissue damage score increased. Administration of Ang 1-7 alone or simultaneously with losartan decreased the levels of aforementioned factors. Also, kidney MDA and nitrate levels significantly increased after I/R induction (P < 0.05). According to the results of this study, it can be claimed that the effect of losartan in the presence of Mas receptor is statistically significant and kidney damage dramatically decreases.